Basic Shape dalam Desain Mebel Taman Bacaan Anak di Surabaya - Dominica Giovanna (Intra, 2017)
The establishment of the 'Taman Bacaan Anak' that becoming the trend nowadays, aimed to realize the city of Surabaya as literacy [7]. However, the